2003
DOI: 10.1210/me.2003-0074
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of Normal and Mutated Steroidogenic Acute Regulatory Proteins in the Mitochondria: the Fate of Unwanted Proteins

Abstract: Steroidogenic acute regulatory protein (StAR) is a nuclear encoded mitochondrial protein that enhances steroid synthesis by facilitating the transfer of cholesterol to the inner membranes of mitochondria in hormonally regulated steroidogenic cells. It is currently assumed that StAR activity commences before or during StAR import into the mitochondrial matrix. The present study was designed to demonstrate that, once imported and becoming physiologically irrelevant, exhaustive accumulation of StAR must be limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 66 publications
9
60
1
1
Order By: Relevance
“…The striking down-regulation of the expression of the rate-limiting step enzyme of steroidogenesis StAR during the early stages of adrenal regeneration fits well with the reduced gland steroidogenic capacity. It is reasonable to conceive that at day 5 post-surgery highly proliferating adrenocortical cells are unable to produce adequate amounts of StAR, whose expression rapidly decrease due to its rather short half-life (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The striking down-regulation of the expression of the rate-limiting step enzyme of steroidogenesis StAR during the early stages of adrenal regeneration fits well with the reduced gland steroidogenic capacity. It is reasonable to conceive that at day 5 post-surgery highly proliferating adrenocortical cells are unable to produce adequate amounts of StAR, whose expression rapidly decrease due to its rather short half-life (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MG115 has been reported to cause a complete blockade of G1/S and metaphase transitions, as well as a delayed progression through S phase in various cell types cultured in vitro (34). Several in vitro experiments showed that relatively high concentrations of proteasome inhibitors are needed to inhibit proteasome-dependent StAR protein degradation (5,6,8). Hence, our present negative findings may depend on the relatively low doses of inhibitors administered in our in vivo experiments, coupled to the rapid inactivation of the inhibitors due to their rather short half-life (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein stability is a key regulatory mechanism in the control of cell development, the cell cycle, cell growth, and apoptosis. Proteolysis of mitochondrial proteins is regulated by multiple mechanisms (35,36). The ubiquitin/proteasome system regulates molecules such as Mcl-1, a member of the Bcl-2 family in mitochondria (37)(38)(39)(40), indicating the importance of the protease system in the regulation of levels of Bcl-2 family proteins.…”
Section: Discussionmentioning
confidence: 99%